Cost of quality and quality performance: a case of Universiti Teknologi MARA (UiTM), Dungun, Arau and Segamat Branch Campuses / Jamalludin Helmi Hashim - Helmi Hashim, Jamalludin (2001)
This study intends to identify measurement of the Cost of Quality as the main issue quality activity. This study will adopt Juran (1960) model on Cost of quality and relate the model to measure quality performance. The objectives of the study are: to determine the cost of quality in Universiti Teknologi MARA (UiTM) according to the cost of quality components; to determine the collection methods that are used to collect the cost of quality; and to determine the relationship among the three quality cost components using "Prevention-Appraisal-Failure" (PAF) model. The study was conducted by interviewing the Head of Quality (Coordinator), Assistant Treasurer in the respective branch campuses and Centre of Total Quality Education in Shah Alam in order to gather the qualitative and quantitative data. It is found that the Prevention Cost is the highest portion of the COQ, followed by Appraisal Cost and Internal Failure Cost. UiTM does not identify any External Failure Cost at the time being. The study also revealed that, there is a relationship between conformance and non conformance cost accordance to the Traditional Model of COQ suggested by Ittner (1994). The adjustment on the existing accounting system is in a great need. The Balanced Scorecard, the unique tools of performance indicator is also consider to be a good tool to apply in UiTM as it focus on four key areas: Financial measures; Customer measures; Internal business process measures; and Innovation and growth measures. A study looks into quality issues from a cost behavior's perspective. It is no intentions to solve all problems, or not even the basic, but this is a good starting point to explore further.